Pollen viability, germination and pollination in Myristica fatua Houtt. var. magnifica (Beddome) Sinclair - a threatened taxon of Western Ghats, India - KAVERIAPPA, P RAMA BRAT, K M (Journal of Spices and Aromatic Crops, 1995)
A study of anthesis, pollen viability and pollination in Myristica fatua var. magnifica showed that anthesis took place early in the morning and anther dehiscence about 36-48 h prior to anthesis. The pollen grains held inside the flower get released as a cloud at the time of anthesis. Male flowers are shed 36-48 h after anthesis. The pollen grains are sticky, pilated in sculpture, spherical and without any visible aperture. Pollen germination commenced 2 h after dusting the grains on slides containing sucrose solution and was completed in about 6 h. Maximum germination (67.3 per cent) was obtained in 5% sucrose solution and the length of pollen tube was also maximum in this concentration. The stained and unstained pollen grains varied in size and the former measured more than the latter. The viability of freshly collected pollen as determined by their stainability in acetocarmine was 94.3 per cent. Among the 10 species of insects collected from trees during flowering, Cremastogaster sp., Sima nigra and Syrphissp. were most common.